Efisiensi Proses Produksi Sandal dengan Process Mapping and Analysis (Studi Kasus Pada CV AWMK) - Asni Mustika Rani (Universitas Islam Bandung, 2018)
Every business is defined by its various processes. These processes determine capabilities including what the organization can and cannot do regarding the types of product value delivered to customers. CV AWMK is a company that produce sandals. This company uses production system by order or making sandals according to design and order quantity. It is important for the company to reassess each activity that goes on fundamentally, so that the company can redesign the production process for continuous improvement. Process mapping and analysis is a technique for documenting activities in a detailed, compact, and graphic form to help company make improvement in their overall processes and products. The purpose of this study is to analyze the current production process in CV AWMK, and applied process mapping and analysis methods to make efficiency of production process. The results showed that the process mapping and analysis can minimize production time and improve efficiency 20% than before.